Escuela de Ciencias Sociales y Humanidades. (UNED, 2024)
Al fondo a la izquierda de camisa blanca José Luis Torres Rodríguez, seguido de Rodrigo Salas de la Paz, Carlos Benavides Barquero, Patricia Rodríguez, Mercedes Mesén Valverde, Jeannette Vargas Jiménez, Hernán Cordero González, Mercedes Vargas Ramírez.